2018
DOI: 10.1371/journal.ppat.1007056
|View full text |Cite
|
Sign up to set email alerts
|

The Hyr1 protein from the fungus Candida albicans is a cross kingdom immunotherapeutic target for Acinetobacter bacterial infection

Abstract: Different pathogens share similar medical settings and rely on similar virulence strategies to cause infections. We have previously applied 3-D computational modeling and bioinformatics to discover novel antigens that target more than one human pathogen. Active and passive immunization with the recombinant N-terminus of Candida albicans Hyr1 (rHyr1p-N) protect mice against lethal candidemia. Here we determine that Hyr1p shares homology with cell surface proteins of the multidrug resistant Gram negative bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(66 citation statements)
references
References 83 publications
(93 reference statements)
3
63
0
Order By: Relevance
“…Our group uses advanced computational molecular modeling and bioinformatic approaches to discover novel vaccine antigen candidates that target more than one high priority human pathogens 14,25,26 . This strategy, known as unnatural or heterologous immunity, has been previously applied in the development of viral and bacterial vaccines in which an antigen protects against another pathogen from the same or from a different kingdom 25 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our group uses advanced computational molecular modeling and bioinformatic approaches to discover novel vaccine antigen candidates that target more than one high priority human pathogens 14,25,26 . This strategy, known as unnatural or heterologous immunity, has been previously applied in the development of viral and bacterial vaccines in which an antigen protects against another pathogen from the same or from a different kingdom 25 .…”
Section: Discussionmentioning
confidence: 99%
“…A recombinant form of N-terminus of the Als3p (rAls3p-N) elicits robust Tand B-cell responses and protects mice from both Candida and MRSA infections 26,[28][29][30][31][32][33] . Most recently, we reported that another hyphal cell surface protein of C. albicans, Hyr1p, has 3-D structural homologies with candidate antigens of the MDR GNB A. baumannii 14 . Indeed, using different mouse models, active or passive immunization (with pAb) targeting either Als3p or Hyr1p, protected mice from S. aureus or A. baumannii infections, respectively 14,26,28 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations